Filter media modeling applying Voronoi-Laguerre diagrams - Duarte, Roberto C. (2023)
The processes of separating pollutant particles in liquids and gases are crucial processes in many industries. There are different approaches to modeling these processes, including 2D and 3D models. Some disadvantages of these models range from not accurately fitting the real complexity of the problem, and other models that improve this can be very computationally complex. The proposal of this work is a computational model based on a multi-layered filtering medium constructed using Voronoi-Laguerre diagrams to represent non-woven fibrous materials. Monte Carlo simulations were used to estimate the filter efficiency under different process conditions and with statistical analysis. The results are consistent with the general theory of filtration and allowed the captured particles to be located in pores or fibers, enabling visualization of the 3D structure of the filtering medium. Moreover, this model has the potential to estimate the topological properties of the filtering medium, such as tortuosity and connectivity. Future work is required to improve the computational time for generating the models.